Stability analysis of sodium saccharin in fried nuts and seeds—Determination of sodium saccharin and o-sulfamoylbenzoic acid by HPLC - Mu, Li; Liu, Qianqian; Sun, Sijia; Liu, Yuhang; Gao, Zeyue; Zhang, Li; Xu, Ying; Li, Gang (Frontiers in Nutrition, 2025)
Since the invention of synthetic sweeteners, there has been considerable debate regarding the safety of some of these sweeteners due to their poor thermal stability. Sodium saccharin is a synthetic sweetener used to modulate the flavor of fried nuts and seeds. The change in saccharin sodium during high-temperature frying was investigated, and a detection method for saccharin sodium and its frying product, o-sulfamoylbenzoic acid, was established using high-performance liquid chromatography (HPLC). Sodium saccharin will be completely decomposed at 190 °C for 40 min by frying. O-sulfamoylbenzoic acid is the decomposition product of sodium saccharin under high-temperature frying conditions. An HPLC method was developed for the simultaneous determination of sodium saccharin and o-sulfamoylbenzoic acid. When the UV wavelength was 264 nm, the mobile phase was an acetonitrile-0.1% formic acid aqueous solution with gradient elution, and the detection was performed using HPLC. The detection limit of sodium saccharin was 0.045 mg/kg, and the limit of quantification (LOQ) was 0.135 mg/kg. O-sulfamoylbenzoic acid showed a detection limit of 0.056 mg/kg and a limit of quantification of 0.167 mg/kg. The recovery rate of spiked sodium saccharin ranged from 105.67 to 112.16% with relative standard deviations (RSDs) between 0.24 and 1.39%. The recovery rate of o-sulfamoylbenzoic acid spiked between 98.67 and 108.16% with relative standard deviations (RSDs) ranging from 0.13 to 1.51%. We employed the established method to conduct application detection and analysis of a range of commercially available snack foods. Saccharin sodium was detected, while o-sulfamoylbenzoic acid was not found.